Vaping while high: Factors associated with vaping marijuana among youth in the United States. (1st December 2020) - Ben Taleb, Ziyad; Kalan, Mohammad Ebrahimi; Bahelah, Raed; Boateng, Godfred O.; Rahman, Mashikur; Alshbool, Fatima Z.
Highlights: Large proportion (26.2 %) of U.S. youth have ever vaped marijuana in 2018. Vaping marijuana was associated with tobacco products use of cigarette, e-cigarette, hookah and cigar. The odds of vaping marijuana increase as lifetime use frequency of e-cigarette increases. Abstract: Introduction: The use of e-cigarette and other vaping devices have become popular among youth in US. In addition to nicotine, vaping devices can be used to vaporize marijuana. However, factors associated with vaping marijuana among youth remain unexplored. This study examined the rates of vaping marijuana and its correlates among youth in the US. Methods: We conducted a cross-sectional analysis of survey data from the 2018 National Youth Tobacco Survey of middle-and high-schoolers who provided information regarding ever use of vaping devices to vape marijuana (n = 10, 680). Multivariable regression model was conducted to assess factors associated with vaping marijuana. Results: Overall, 26.2 % of participants reported ever vaping marijuana. High-schoolers [vs middle-schoolers; aOR = 2.16, 95 %CI:1.76−2.67], Hispanics [vs Whites; aOR = 2.30, 95 %CI:1.90−2.80], and Blacks [vs Whites; aOR = 1.42, 95 %CI:1.04−1.92] were more likely to ever vape marijuana. Those who perceived e-cigarette as equally addictive to cigarettes, were less likely to ever vape marijuana [aOR = 0.79, 95 %CI:0.65−0.97]. In addition, those who reported ever trying cigarettes [aOR = 1.63, 95 %CI:1.29−2.06], cigars [aOR = 2.62, 95 %CI:2.08−3.30], or hookah [aOR = 2.88, 95 %CI:2.14−3.89] were more likely to ever vape marijuana. Lifetime frequency of e-cigarette use was associated with greater odds of ever vaping marijuana (p-values <0.001). Conclusion: Large numbers of youth in the US have ever vaped marijuana. Our findings indicate that sociodemographic characteristics, tobacco product use, frequency of e-cigarette use are important factors associated with vaping marijuana. Tobacco control campaigns targeted at curbing the use of e-cigarette and other vaping devices among youth in the US should be extended to address vaping substances other than nicotine such as marijuana.